2018
DOI: 10.5539/elt.v11n8p143
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Oral Corrective Feedback on Article Errors in L3 English: Prompts vs. Recasts

Abstract: This study examines the effect of prompts and recasts in providing CF for the article errors by Kurdish-Arabic bilinguals who learn English as a third language. 39 lower-intermediate Kurdish-Arabic bilingual learners of English were tested on three tests: pre-, post-, and delayed post-tests. The participants were randomly put into three groups: (1) prompt group (n =15), (2) recast group (n = 14), and (3) no feedback group (n = 10). Each group completed 28 dialogues, which included articles in a Forced Choice E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…According to Doski & Cele (2018), OCF becomes one favorite methods in teaching speaking. All students performed significantly better after the teachers responded to their speaking by providing OCF, especially for the use of articles in English.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Doski & Cele (2018), OCF becomes one favorite methods in teaching speaking. All students performed significantly better after the teachers responded to their speaking by providing OCF, especially for the use of articles in English.…”
Section: Resultsmentioning
confidence: 99%
“…Lyster and Ranta (1997) observed diverse types of corrective feedback that the teachers give on the students' errors and try to examine the students' uptake, a clue that students have already noticed and known what the feedback means. Feedback can establish the contribution and procedural knowledge from cognitive approaches (Doski & Cele, 2018). There are six types of oral corrective Journal of Research on English and Language Learning is licensed under a Creative Commons Attribution 4.0 International License feedback mentioned by Lyster and Ranta.…”
Section: Oral Corrective Feedbackmentioning
confidence: 99%
“…It seems that contrasting prompts and recasts, the method employed in the study we are replicating (Yang & Lyster, 2010), was also a motivation for some later studies that used the same or similar design. Doski and Cele (2018) investigated the effects of recasts and prompts on article errors in English learned as a third language by primary school children (sixth grade, 11–12 years old) in Kurdistan. In their study of 39 lower‐intermediate Kurdish–Arabic bilinguals, the authors found that both recasts and prompts were more effective than no feedback, but on a delayed posttest, the prompt group outperformed the recast group, which indicated that prompts had longer lasting effects.…”
Section: Background Literaturementioning
confidence: 99%
“…Given the profile of the participants and the number of years of English study, we felt confident that the participants would be familiar with the 2,000 most frequent words in English. To ensure that the materials would not pose comprehension problems due to unfamiliar vocabulary, we ran the materials through the lexical profiler at http://www.lextutor.ca/vp/ (Cobb, 2019) and found that 97-98% of the words in each story, with the exception of Cinderella, 9 were within the 2,000 most frequent words. We then showed the stories to the teachers, and they confirmed that the students should not have comprehension problems.…”
Section: Modificationsmentioning
confidence: 99%
“…Research focusing on the English language has explored the efficacy of different CF types for learning a range of morpho-syntactic structures, e.g. articles (Doski and Cele 2018;Muranoi 2000;Nassaji 2017;Sheen 2008); regular past tense forms (Doughty and Varela 1998;; regular versus irregular past (Yang and Lyster 2010); regular past versus comparative adjectives (Ellis 2007); possessive determiners his/her (Ammar and Spada 2006); third person singular -s and possessive determiners his/her (Sato and Loewen 2018); question formation (Mackey and Philp 1998;McDonough and Mackey 2006;Philp 2003); past progressive (Révész 2009(Révész , 2012; passive voice (Li et al 2016); prepositional and double object datives (McDonough 2006); locative prepositions (Nakatsukasa 2016), 'that' trace filter in English (Goo 2012). Research into the effects of CF on learning languages other than English has been less frequent (e.g.…”
Section: Introductionmentioning
confidence: 99%